Cadmium Uptake and Distribution in Fragrant Rice Genotypes and Related Consequences on Yield and Grain Quality Traits - Adam Sheka Kanu; Umair Ashraf; Zhaowen Mo; Issaka Fuseini; Lamin R. Mansaray; Meiyang Duan; Shenggan Pan; Xiangru Tang (Journal of Chemistry)
Cadmium (Cd) toxicity has varying consequences on plants growth and development. This research focused on examining the influence of Cd toxicity on fragrant rice genotypes and its consequences on yield, yield related parameters, and grain quality traits. Randomized complete block design comprising five different fragrant rice cultivars (Meixiangzhan 2, Xiangyaxiangzhan, Guixiangzhan, Basmati, and Nongxiang 18) and four Cd levels (0, 50, 100, and 150 mg/kg soil) was used. The results showed that, with increased levels of soil Cd toxicity, Cd uptake in roots and distribution to other organs increased in dose dependent manner. Uptake and accumulation were higher in roots than in shoots with the highest uptake in both roots and shoots observed in Meixiangzhan 2, followed by Nongxiang 18, Basmati, Xiangyaxiangzhan, and Guixiangzhan cultivars. With increased Cd toxicity, yield and yield parameters were affected in all cultivars. Grain quality was also found affected under Cd stress condition. The results suggested that soil Cd toxicity has negative consequences on rice performance and uptake varies among cultivars. Conclusively, Cd toxicity impaired rice yield formation and grain quality by altering yield components (panicles number, spikelet per panicles, and spikelet setting (%)); however, Guixiangzhan variety performed better, while Meixiangzhan 2 performed less in terms of minimum Cd uptake and distribution to grains, yield, and grain quality reduction under Cd stress condition.